Fractals in soil science - Pachepsky, Y. (Yakov); Crawford, J. W. (John Wilson), 1963-; Rawls, Walter J. (Developments in soil science, 2000)
This book presents the state-of-the-art after fifteen years of exponentially growing applications of fractal geometry in soil science. It demonstrates the wide-ranging applicability of fractal models in soil science and indicates new opportunities to integrate processes in soils within or across scales using fractals. Contributed by some of the pioneers in the field, chapters represent a broad spectrum of applications from geochemistry to microbiology and from scales of micrometers to the landscape, and serve as an introduction to the subject. Topics include fractal aspects of soil structure, porosity and texture, scaling in preferential and hydraulic conductivity, anoxic volumes and adsorption in fractal models of soil, characterization of the pore surface irregularity, fractal properties of soil organic matter, fractal concepts in studies of soil fauna and mycelium in soils, and fractal analysis of spatial and temporal variability in soil properties and crop yields. A wide spectrum of methods for identifying and measuring fractal properties is introduced and critically discussed. Although the book focussed on solving problems in soil science, the applications and the fractal approach used share much in common with many other fields within and outside of the earth sciences. A unique bibliography on fractals in soils science is included.